Isolation of sesquiterpenes lactone from Curcuma aeruginosa rhizome and the cytotoxic activity against human cancer cell lines - Atun, S.; Arianingrum, R.; Aznam, N.; Malek, S.N.A. (International Journal of Pharmacognosy and Phytochemical Research, 2016)
The objectives of this research were to isolate bioactive compounds from Curcuma aeruginosa Roxb. and to study the cytotoxic activity against human cancer cell lines. The in vitro cytotoxicity test was done on human cancer cell lines such as Breast carcinoma MCF-7 and T-47D; Cervical carcinoma Ca Ski and Hela S3 by MTT ([3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. Cytotoxicity test was also conducted on Vero cells (normal cells). The isolation of bioactive compounds from this extract of C. aeruginosa rhizome was carried out by chromatographic method and the structure elucidation was performed by interpretation of spectroscopic data, including UV, IR, 1H and 13C NMR 1D and 2D. The study showed that n-hexane and chloroform fraction from C aeroginosa had low cytotoxic activity against MCF-7 and Ca-ski (IC50<100µg/mL), but not toxic against Hela S3, T-47D, and Vero cell lines (IC50>500µg/mL). From the chloroform fraction of C. aeroginose we isolated a new sesquiterpene lacton aeruginon (1) and a known compound curcumenon (2). It can be concluded that according to the present study, C. aeruginosa can be used as a potent source of natural bioactive compounds that is rich in sesquiterpene compounds.